PERAN IMPLEMENTASI SP2D BERBASIS KEPATUHAN ATURAN DAN EFEKTIVITAS PENGENDALIAN INTERNAL DALAM MENEKAN TINGKAT RETUR SP2D PADA KPPN SUMBAWA - Dwi Maharani Syahputri; Reza Muhammad Rizqi (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the role of compliance with norms and the effectiveness of internal control in reducing the rate of SP2D returns at KPPN Sumbawa. Employing a descriptive qualitative method with a Principal-Agent Theory approach, this research identifies that SP2D returns represent a manifestation of agency costs arising from information asymmetry and failures in operational risk management at the work unit level. The study population encompasses all work units under the jurisdiction of KPPN Sumbawa, with purposive sampling involving key informants from both KPPN and the work units. Data analysis was conducted through content analysis of interview transcripts and SP2D return monitoring documents for the year 2024. The findings indicate that the dominant cause of returns is inactive or closed recipient accounts, frequently attributable to excessive staff workload and a lack of proactive risk evaluation. Although compliance with norms is relatively high due to routine KPPN oversight, weaknesses in internal control at the initial level (the SAKTI application) remain a critical gap. This study concludes that achieving a zero-return objective necessitates mandatory systemic validation mechanisms and a reorientation of human resource competencies. This research contributes to the development of public sector internal control strategies and offers practical recommendations for treasury system integration to enhance state liquidity efficiency. Keywords: Agency Theory, Internal Control, Regulatory Compliance, Returns